Impact of the Lung Allocation Score - McShane, Pamela J.; Garrity, Edward R., Jr. (Seminars in Respiratory and Critical Care Medicine, 2013)
The number of donors falls short of the number of patients on the wait list for lung transplantation making it necessary to ration the available donor organs. The ideal allocation system is guided by ethical principles and scientifically accurate at identifying patients who will gain the greatest degree of benefit from receiving the organ, in terms of both pre- and posttransplantation survival. The lung allocation score (LAS) was developed in 2005 to reduce mortality on the wait list, prioritize candidates based on urgency, minimize the role of geography, and maximize transplant benefit. The LAS has not made much of an impact on the geographic disparity of listing patients for lung transplantation, but it did achieve the goal of reducing wait-list mortality and prioritizing patients based on urgency. In prioritizing patients with the most urgent status, a new controversy has come into the forefront: whether or not the increased number of critically ill recipients maximizes transplant benefit. Despite the controversy, the LAS system is an improvement compared with the traditional first-come, first-served system, and it has even been adopted by Eurotransplant. In the future, as modifications are made to improve the LAS, the issue of critically ill patients and maximizing posttransplant benefit will be the focus.
Keywords: lung allocation score; lung transplantation; priority score; lung donors